2018
DOI: 10.1002/pro.3372
|View full text |Cite
|
Sign up to set email alerts
|

Lactose repressor hinge domain independently binds DNA

Abstract: The short 8–10 amino acid “hinge” sequence in lactose repressor (LacI), present in other LacI/GalR family members, links DNA and inducer‐binding domains. Structural studies of full‐length or truncated LacI‐operator DNA complexes demonstrate insertion of the dimeric helical “hinge” structure at the center of the operator sequence. This association bends the DNA ∼40° and aligns flanking semi‐symmetric DNA sites for optimal contact by the N‐terminal helix‐turn‐helix (HtH) sequences within each dimer. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(287 reference statements)
1
5
0
Order By: Relevance
“…This analysis shows that the binding domain is indeed flexible, with a variety of conformations sampled during the simulation. In addition, in agreement with previous studies, 87 it appears that the DNA binding helices are capable of moving independently of each other, which likely affects the search process on the DNA. This is particularly interesting, because the hinge sequence itself may also contribute substantially to the binding affinity for both specific and nonspecific DNA, while also playing an important role in the transition from nonspecific to specific binding.…”
Section: ■ Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…This analysis shows that the binding domain is indeed flexible, with a variety of conformations sampled during the simulation. In addition, in agreement with previous studies, 87 it appears that the DNA binding helices are capable of moving independently of each other, which likely affects the search process on the DNA. This is particularly interesting, because the hinge sequence itself may also contribute substantially to the binding affinity for both specific and nonspecific DNA, while also playing an important role in the transition from nonspecific to specific binding.…”
Section: ■ Introductionsupporting
confidence: 91%
“…The observed changes in the hinge helices in the simulations of free LacI are of interest, as the HTH motif observed in LacI (Figure ) is a common feature of many DNA-binding proteins, , and the formation of the hinge helices has been argued to be an important feature for DNA bending in various lac repressor-operator complexes. , It has also been argued that the protein–DNA interface of the nonspecific complex is flexible and that this assists in rapid and efficient search for the target site on the DNA . In addition, a recent study has shown that the LacI hinge domain independently binds DNA, with the hinge region mediating both specific and nonspecific binding, with only small differences in affinity between the two. Following from this, computational studies have suggested that the hinge region plays an important contribution to the electrostatic energy of the LacI-DNA complex, the salt dependence of this electrostatic energy, and the number of salt ions excluded as the LacI-DNA complex is formed and that the binding of the hinge region of the lac repressor to DNA perturbs networks of correlated motions in the protein that in turn regulates its DNA binding affinity …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…83,86 It has also been argued that the protein−DNA interface of the nonspecific complex is flexible and that this assists in rapid and efficient search for the target site on the DNA. 12 In addition, a recent study has shown that the LacI hinge domain independently binds DNA, 87 with the hinge region mediating both specific and nonspecific binding, 87 with only small differences in affinity between the two. Following from this, computational studies have suggested that the hinge region plays an important contribution to the electrostatic energy of the LacI-DNA complex, the salt dependence of this electrostatic energy, and the number of salt ions excluded as the LacI-DNA complex is These values are average values over all 80 nucleotides based on the standard A-DNA and B-DNA forms of the O SymL operator sequence, as generated by the 3DNA web server.…”
Section: ■ Results and Discussionmentioning
confidence: 99%